2018
DOI: 10.1002/mgg3.480
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of next generation sequencing in pediatric practice in Lebanon. A Study on 213 cases

Abstract: BackgroundAccording to the Catalogue of Transmission Genetics in Arabs, less than half of diseases reported in Lebanese patients are mapped. In the recent years, Next Generation Sequencing (NGS) techniques have significantly improved clinical diagnosis, compared to traditional sequencing methods.MethodsA total of 213 analyses by NGS (167 by whole exome sequencing (WES) and 46 by multigene panels tests) were performed on pediatric patients across different regions of Lebanon over a period of two years (December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
2
21
2
Order By: Relevance
“…Previously reported nonsense variants, p.R285* and p.R324*, were found in three patients (P15) and (P16‐17), respectively (Henneke et al, 2003; McConnell et al, 1997). Two other previously reported missense variants, p.P332L and p.A137V, were found in (P13) and (P18), respectively (Nair et al, 2018; Nellis et al, 2003). Two novel frameshift variants due to a single base deletion or insertion (c.287delA, c.908insA) were found in two sets of unrelated patients (P19 and P20) and (P21 and P22), respectively.…”
Section: Resultsmentioning
confidence: 80%
“…Previously reported nonsense variants, p.R285* and p.R324*, were found in three patients (P15) and (P16‐17), respectively (Henneke et al, 2003; McConnell et al, 1997). Two other previously reported missense variants, p.P332L and p.A137V, were found in (P13) and (P18), respectively (Nair et al, 2018; Nellis et al, 2003). Two novel frameshift variants due to a single base deletion or insertion (c.287delA, c.908insA) were found in two sets of unrelated patients (P19 and P20) and (P21 and P22), respectively.…”
Section: Resultsmentioning
confidence: 80%
“…Several studies provided only representative case examples documenting outcomes of interest. [16][17][18][19] We summarize the number of studies with N ≥ 20 patients documenting the outcomes of interest and representative examples of reported health outcomes and clinical impacts for each subcategory.…”
Section: Outcomes Of Es/gs For Ca or Dd/idmentioning
confidence: 99%
“…Twelve studies reported outcomes following ES/GS that had an impact on family members of the patient, such as cascade genetic testing, referral to specialists, or changes in clinical management resulting from the diagnosis of a previously unknown disorder. 7,11,16,19,26,27,31,32,34,41,42,48 In a cohort of 62 families with congenital anomalies of kidney and urinary tract (i.e., CAKUT) who had ES, first-degree relatives of 1 patient were referred for ophthalmological assessment in light of a diagnosis of renal coloboma. The authors reported optic nerve abnormalities were identified in relatives who were PAX2 variant carriers.…”
Section: Family-focused Outcomesmentioning
confidence: 99%
“…The frequency of this variant is unknown in the Lebanese population and the variant was absent from our in-house WES database of 339 individuals as well as in our recent study of 167 patients who underwent WES analysis. 13 The variable clinical description necessitates reporting recurrent variants. This study emphasizes the importance of next generation sequencing in providing a fast and accurate clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%